621 PL02.05 LONG-TERM TREATMENT OF PATIENTS WITH EOSINOPHILIC GASTRITIS AND/OR EOSINOPHILIC DUODENITIS WITH LIRENTELIMAB, A MONOCLONAL ANTIBODY AGAINST SIGLEC-8. (17th September 2021) - Peterson, Kathryn; Chehade, Mirna; Murray, Joseph; Falk, Gary; Gonsalves, Nirmala; Genta, Robert; Rothenberg, Marc; Bledsoe, Adam; Durrani, Sandy; Vaezi, Michael; Shaw, Camilla; Rasmussen, Henrik; et al.
Abstract: : Eosinophilic esophagitis (EoE), gastritis (EG), and/or duodenitis (EoD) are associated with accumulation and activation of eosinophils and mast cells in the esophagus, stomach, and/or duodenum, respectively. Lirentelimab (AK002), an antibody against siglec-8, depletes eosinophils and inhibits mast cells. We performed an open-label extension (OLE) study of subjects who completed ENIGMA (a randomized, double-blind, placebo-controlled phase 2 study of lirentelimab in adults with symptomatic, biopsy-confirmed EG and/or EoD, with or without EoE) to evaluate long-term responses. Methods: Subjects who received 4 monthly infusions of lirentelimab or placebo during ENIGMA (n = 59) were eligible for the OLE; they received monthly, escalating doses of lirentelimab (0.3 or 1 mg/kg escalating to 3 mg/kg). Symptoms were assessed weekly using an electronic daily patient-reported outcome questionnaire and total symptom scores (TSS) were calculated. Patients underwent upper endoscopy with biopsy at screening and at the end of ENIGMA (day 99, week 16, blinded); in the OLE, endoscopies were performed on day 323 (30 weeks after the first dose in the OLE). Histopathology was assessed by a single pathologist. Results: Fifty-eight subjects entered the OLE; 45 completed ≥52 weeks lirentelimab (including exposure during ENIGMA) and 29 completed 70 weeks. Mean TSS improved through week 70 (Figure 1). Subjects receiving 70 weeks lirentelimab (ENIGMA+OLE) had further improvements in TSS from baseline (mean reductions: 68% at weeks 29–30, 70% at weeks 51–52, 75% at weeks 69–70). Symptom scores (abdominal pain, nausea, vomiting, early satiety, appetite loss, abdominal cramping, bloating, diarrhea) decreased significantly from baseline. Treatment response was not associated with concomitant EoE. The most common adverse event was mild to moderate infusion-related reactions, usually with the first infusion. Conclusion: In the OLE of the ENIGMA study, patients with EG and or EoD (with or without concomitant EoE) who received lirentelimab had sustained tissue eosinophil depletion and significant long-term symptom improvement. Symptoms continued to improve with duration of treatment. Lirentelimab appears to be a promising targeted treatment for EG and/or EoD.